Self-propelled Leidenfrost droplets on a heated glycerol pool - Ryo Matsumoto (Nature Portfolio, 2021)
Abstract The development of contactless sample manipulation for microfluidic purposes has attracted significant attention within the physicochemical fields. Most existing studies focus on the interactions of unheated liquid substrates and on heated/unheated solid substrates. Therefore, the dynamics of droplets on heated liquid pools have yet to be explored. Here, we present an experimental investigation on the levitated and self-propelled droplets on a heated pool. We aim to identify the effect of the pool temperature and the thermophysical properties of droplets on the dynamics of a self-propelled Leidenfrost droplet on a heated pool. The motion of droplets after levitation on the heated pool is visualized. To elucidate the self-propulsion of Leidenfrost droplets, we quantify the thickness of the vapour film between the approaching droplet and the pool surface. Our experimental results show a quantitative agreement with the simple model prediction for self-propelled Leidenfrost droplets. Our results provide deeper physical insights into the dynamics of Leidenfrost droplets on a heated pool for contactless and contamination-free sample manipulation.